Морфометрія генеративних особин та віталітетна структура популяції Pedicularis exaltata Besser (Orobanchaceae) в Буковинському Прикарпатті - Бурлака, М.Д.; Каземірська, М.А. (Український ботанічний журнал, 2012)
В статье представлены результаты исследования популяции Pedicularis exaltata в окрестностях г. Черновцы. Детально описано и проанализировано основные морфометрические пара метры генеративных особей вида, дана виталитетная оценка популяции, перечислены угрозы и определена степень их влияния на нее. The article presents the results of investigation of Pedicularis exaltata population near Chernivtsi. Detailed description and analysis of main morphometric parameters of the species’ generative individuals as well as the results of vitality analysis are given. Major threats for the population are listed and the level of their influence is examined.